How to Design Genetic Biosensors for Medical Purposes? - Shirvani-Farsani, Zeinab; Mehrab Mohseni, Mahdieh (Asian Pacific Journal of Cancer Biology, 2025)
Genetic biosensors lead to a revolutionary integration of genetic engineering and biosensing techniques, suggesting high precision in molecular diagnostics and personalized medicine. These tools use nucleic acids and proteins to enabling early disease diagnosis, and real-time scanning of biological procedures like cancer. Their high sensitivity, specificity, and adaptability make them promising for clinical applications in spite of challenges in optimization and scalability. This review explores the design principles, technological advancements, and biomedical applications of genetic biosensors, focusing on their potential to improve healthcare through personalized medicine and more progress therapeutic interventions.